Analysis of the Arabic Orthography of the Archipelago in Madura: Text, Characteristics and Meaning - Wiranto Talibo; Inunu, Anggun; Anggie Potale; Suharia Sarif; Damhuri (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2025)
This study aims to describe and analyze the orthographic system of Madurese Arabic Pegon, as reflected in three primary manuscripts used in pesantren traditions: Safinatun Najah, Bulughul Maram, and a handwritten translation of section 677. A qualitative approach was employed using descriptive-analytical and philological methods. Data were collected through manuscript observation, transliteration, and document analysis, and examined using philological, orthographic, and semiotic frameworks. The findings indicate that Madurese Pegon displays an adaptive graphemic structure characterized by modified letters such as ڠ, ﭖ, ڽ, and ﭺ that represent local phonemes. Its vocalization system is flexible and relies on readers’ competence within pesantren learning practices. The analysis further shows that Pegon functions as a pedagogical and hermeneutic tool, bridging classical Arabic texts with local language and culture. This study addresses a gap in research on Pegon orthography in Madura. It affirms its role in shaping linguistic and religious identity. The results underscore the urgency of preserving Pegon and the potential to expand interdisciplinary studies of Nusantara Islamic writing traditions.